Motivational reasons of personality's life activity - Shvalb, Y. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
This article analyzes the major theories of motivation and released three approaches: biological (or organic), cultural and personal. It is shown that in each of them the concept of motivation connected with special "frame" construct that provides the allotment of relevant spheres: need- motivational, value-motivational and sense-motivational. The author claims that all of these approaches are legitimate to use only for description and explanation of individual behaviour or activity acts. Noted, that the transition to the analysis of integrity phenomena of life and life-activity needs another description of the motivational sphere of personality. And this way of description cannot be lead down to the united definition of motivation. Author proposed the model of motivational sphere, based on two criteria, which a set by several components. The first criterion is a relation of activity of the individual psychological sources which is presented in the form of intentions. And the second consists of the forms of representation motivators in individual consciousness.
Keywords: motivation; needs; values; ideals; meaning; intention; livelihoods; lifestyles